Name etymology and its symbolic value in Francis Scott Fitzgerald's "The great Gatsby" - Avsenak, Vanja (Acta neophilologica, 2003)
The aim of my paper is to scrutinize the manifold interpretations of proper names and their possible symbolical value that the reading of F. S. Fitzgerald's classic leaves in the reader. On the whole, the novel's internal structure is rather comprised, which consequently makes the story exact, its plot condensed, but behind this seemingly concise and more or less simple language the author nevertheless manages to embody powerful symbolism that speaks for itself. It is disputable whether Fitzgerald truly aimed to produce such a strong metaphorical emphasis that would most minutely delineate America's social character in the turbulent twenties as projected in the personal stories of the novel's leading protagonists. Within this figurative scope, large as it is, I therefore focus only on the significance of proper names and their obvious contribution to the holistic social portrayal. It may be only a minor, but nevertheless one of the most reliable and crucial means of outlining the consequences of the postwar spiritual apathy that overwhelmedthe American nation and was induced by the societal downfall due tothe disillusion of the American Dream. How this Dream influenced each individual's and society's destiny remains to be my goal in this article. For the purpose of analysis I rely on the 1994 Penguin edition. All direct quotes from now on are to be taken from this source.
Keywords: American literature; ameriška književnost; Fitzgerald, Francis Scott, 1896-1940; osebna imena; simbolika